The expression of the concepts of dolus and culpa in Chinese legal language: distinctive features and criticalities - Colangelo, Lara (Comparative Legilinguistics, 2023)
The ‘migration’ of concepts from one language to another, which takes place in cultural exchange, frequently gives rise to changes in the target language, primarily involving the lexical field. The reception of the Romanist legal tradition in China has led to the formation of a specialized lexicon which, along with the translation and production of Roman law-related works, has been subject to constant growth. This kind of terminological transposition has often resulted in the emergence in Chinese of more than one translatant for the same Latin word. As a concrete example of this phenomenon, this paper aims at providing a synoptical overview of the rendering in Chinese of the concepts of dolus and culpa, two legal institutions also largely connected to the field of commercial law. The sources analyzed from a diachronic and contrastive perspective range from the earliest manuals of Roman law published in China at the beginning of the twentieth century to recent documents, translated or directly composed in Chinese. More specifically, this paper will try to answer the following questions: what is the historical evolution of the main terms used in Chinese to express the concepts of dolus and culpa? What are the criteria adopted by Chinese translators/authors in choosing these terms? What are the main features and issues related to the linguistic rendering of the two legal institutions? As for the results of this study, attention will be paid to one of the peculiarities of the linguistic rendering of the concept of culpa, that is the use of two different translatants: guoshi 过失 and guocuo 过错. At the same time, another aspect on which this paper will shed light is the existence of a plethora of translatants related to the concept of dolus (qizha 欺诈, guyi 故意, zhaqi 诈欺, etc.). In this sense, on the one hand, it will be shown how the presence of multiple translatants is acceptable and useful when they are used to express the different shades of meaning conveyed by dolus and culpa that cannot be rendered by means of one single translatant for each of these two notions; on the other hand, this paper will highlight the necessity of a higher homogeneity and standardization of the Chinese Romanist lexicon.